Editor's note: Family roadmap through Corona - Navabinejad , Shokouh (Applied Family Therapy Journal (AFTJ), 2020)
Coronavirus is not just a disease, it has had its effects on the economy, culture, and even the family at the micro and macro levels, and has led to dramatic positive and negative changes in some areas. The family is one of the institutions that has been greatly affected by the pandemic of this virus, positive and negative effects that indicate the positive and negative characteristics of different families; But in the end, the corona can provide families with an unparalleled opportunity to correct some of the trends and interactions within the family, if viewed properly. Among these positive effects, most of all, is the love, motivation and appetite for acquiring daily knowledge and information related to the sciences related to the Corona epidemic, which we observe among different sections of society, and this is a place of hope and a good sign. Education is broadcast in the media and more widely in cyberspace. All of them are eager to know the latest scientific findings on the virus and thus raise their awareness of the disease, but this quarantine has provided unique opportunities for family members.